Tales from outer suburbia - Tan, Shaun (New York, NY : Arthur A. Levine Books, 2009)
Fifteen illustrated short stories, some humorous and some haunting, set in the Australian suburbs.
The water buffalo -- Eric -- Broken toys -- Distant rain - - Undertow -- Grandpa's story -- No other country -- Stick figures -- The nameless holiday -- The amnesia machine -- Alert but not alarmed -- Wake -- Make your own pet -- Our expedition -- Night of the turtle rescue.
Accelerated Reader/Renaissance Learning
A Junior Library Guild selection
Keywords: Children's stories, Australian; Suburban life -- Australia -- Juvenile fiction; Suburban life -- Australia -- Fiction; Short stories; Australia -- Juvenile fiction; Australia -- Fiction